Does the Severity of Hangovers Decline with Age? Survey of the Incidence of Hangover in Different Age Groups. (13th September 2013) - Tolstrup, Janne S.; Stephens, Richard; Grønbæk, Morten
<x xml:space="preserve">Abstract</x> Background Alcohol hangover is a growing research area, but differences across the life span have not been assessed. Here, we test the hypothesis that the severity of hangovers depends on age. Methods A cross‐sectional study of 51, 645 men and women aged 18 to 94 years old, who participated in the population‐based Danish Health Examination Study (DANHES) in Denmark between 2007 and 2008, formed the database for our study. Results The incidence of severe hangover was lower among older than younger participants. Odds ratios for experiencing severe hangover following an episode of binge drinking were 6.8, 4.8, 3.0, and 2.0 among the 18 to 29, 30 to 39, 40 to 49, and 50 to 59‐year‐old men, compared with those aged 60+ years. For women, similar results were obtained. This finding could not be explained by the usual amount of alcohol consumption, frequency of binge drinking, or the proportion of alcohol consumed with meals. Conclusions We found that hangover following engagement in binge drinking is much more common in the young than in the older age groups.